Gas Turbine Design, Components and System Design Integration - Schobeiri, Meinhard T.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book written by a world-renowned expert with more than forty years of active gas turbine R&D experience comprehensively treats the design of gas turbine components and their integration into a complete system. Unlike many currently available gas turbine handbooks that provide the reader with an overview without in-depth treatment of the subject, the current book is concentrated on a detailed aero-thermodynamics, design and off-deign performance aspects of individual components as well as the system integration and its dynamic operation. This new book provides practicing gas turbine designers and young engineers working in the industry with design material that the manufacturers would keep proprietary. The book is also intended to provide instructors of turbomachinery courses around the world with a powerful tool to assign gas turbine components as project and individual modules that are integrated into a complete system. Quoting many statements by the gas turbine industryprofessionals, the young engineers graduated from the turbomachinery courses offered by the author, had the competency of engineers equivalent to three to four years of industrial experience.
From the Content: Introduction, Gas Turbines, Applications, Types -- Gas Turbine Thermodynamic Process -- Thermo-Fluid Essentials for Gas Turbine Design -- Theory of Turbomachinery Stages -- Turbine and Compressor Cascade Flow Forces -- Losses in Turbine and Compressor Cascades -- Efficiency of Multi-Stage Turbomachines.
Keywords: Fluid mechanics; Engines; Transportation engineering; Traffic engineering; Engineering Fluid Dynamics; Engine Technology; Transportation Technology and Traffic Engineering